2020
DOI: 10.1155/2020/6381396
|View full text |Cite
|
Sign up to set email alerts
|

The Course of Circulating Small Extracellular Vesicles in Patients Undergoing Surgical Aortic Valve Replacement

Abstract: In the last years, increasing efforts have been devoted to investigating the role of small extracellular vesicles (sEVs) in cardiovascular diseases. These nano-sized particles (30-150 nm), secreted by different cell types, contain signalling molecules that enable participation in intercellular communication processes. In this study, we examined the course of circulating sEVs in patients undergoing surgical aortic valve replacement (SAVR) and correlated them with echocardiographic and standard blood parameters.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 44 publications
0
12
0
1
Order By: Relevance
“…It was suggested that EVs present in the circulation might help cells to maintain hemostasis with assistance of disposal of cellular waste products generated as a result of physical effort; EVs, especially exosomes, released into circulation, could have a role in regulating physiological adaptation processes in response to physical activity and therefore have beneficial health-protective effect. 13 On the other hand, increased concentration of CNVs in isolates from blood was connected with increased risk for blood clot formation in blood vessels and therefrom deriving increased risk for thromboembolic events 39 and also with increased risk for other cardio-metabolic diseases, such as Type 2 diabetes mellitus. 40 Monitoring concentration of CNVs is clinically relevant as it is indicated that it may be informative in assessment of instantaneous risk for thromboembolic events 39 , 40 and glucose tolerance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was suggested that EVs present in the circulation might help cells to maintain hemostasis with assistance of disposal of cellular waste products generated as a result of physical effort; EVs, especially exosomes, released into circulation, could have a role in regulating physiological adaptation processes in response to physical activity and therefore have beneficial health-protective effect. 13 On the other hand, increased concentration of CNVs in isolates from blood was connected with increased risk for blood clot formation in blood vessels and therefrom deriving increased risk for thromboembolic events 39 and also with increased risk for other cardio-metabolic diseases, such as Type 2 diabetes mellitus. 40 Monitoring concentration of CNVs is clinically relevant as it is indicated that it may be informative in assessment of instantaneous risk for thromboembolic events 39 , 40 and glucose tolerance.…”
Section: Discussionmentioning
confidence: 99%
“… 13 On the other hand, increased concentration of CNVs in isolates from blood was connected with increased risk for blood clot formation in blood vessels and therefrom deriving increased risk for thromboembolic events 39 and also with increased risk for other cardio-metabolic diseases, such as Type 2 diabetes mellitus. 40 Monitoring concentration of CNVs is clinically relevant as it is indicated that it may be informative in assessment of instantaneous risk for thromboembolic events 39 , 40 and glucose tolerance. 41 Further studies are needed to improve CNV isolation and assessment methods and to link the measurements of CNVs in isolates from blood to various pathologies.…”
Section: Discussionmentioning
confidence: 99%
“…However, other authors reported a gradual decrease in endothelial EVs at longer time periods post-valvular replacement (1, 3 and 6 months) ( Horn et al, 2015 ; Jung et al, 2017 ), accompanied by an improvement in the endothelial function ( Horn et al, 2015 ) and an increase in platelet EVs ( Jung et al, 2017 ). When it comes to small EVs or exosomes, their numbers acutely decrease after surgical valve replacement (24 h), going back to pre-operative levels 7 days and 3 months post-procedure, suggesting no alteration of small EVs release in response to valvular replacement ( Weber et al, 2020 ). However, in a subgroup of patients, these authors described a positive correlation between increased levels of small EVs and patient-prosthesis mismatch parameters, and suggested the possible prognostic value of small EVs to estimate emerging patient-prosthesis mismatch and adverse outcomes in patients undergoing surgical aortic valve replacement ( Weber et al, 2020 ).…”
Section: Extracellular Vesicles and Cardiovascular Diseasesmentioning
confidence: 99%
“…The role of exosome signaling in valve disease has not been fully studied. However, the levels of extracellular vesicles have been proposed as a biomarker for valve disorders such as calcific aortic valve disease and myxomatous mitral valve disease, and as a prognostic biomarker after surgical aortic valve replacement [147].…”
Section: Valve Diseasementioning
confidence: 99%